Analisis Faktor Yang Mempengaruhi Akuntabilitas Pengelolaan Dana Desa (Studi Pada Desa Kertosari, Jember) - Putri, Maulinda Suryani; Dwi Astuti, Diana; Ilmi, Mainatul (Jurnal Ilmiah METANSI ”Manajemen dan Akuntansi”, 2025)
This study aims to analyze the effect of budget target clarity, village apparatus competence, leadership style, community participation, and reporting system on the accountability of village fund management in Kertosari Village, Jember. This research uses quantitative methods with a survey approach through questionnaires. The population in this study were all village officials and the community in Kertosari Village, Jember. The data collection technique used was simple rondem sampling method using a sample of 60 respondents. The data analysis technique was carried out by multiple linear regression. The results showed that partially the variables of village apparatus competence, leadership style, community participation, and reporting system had a significant effect on the accountability of village fund management and the clarity of budget targets had no significant effect. Meanwhile, simultaneously the variables of budget target clarity, village apparatus competence, leadership style, community participation, and reporting system have a significant effect on the accountability of village fund management. This finding confirms that increasing the competence of village officials, effective leadership, community involvement, and a transparent reporting system play an important role in realizing the accountability of village fund managementand.